KORELASI ANTARA KADAR HbA1c DENGAN LAJU FILTRASI GLOMERULUS (LFG) PADA PASIEN DIABETES MELITUS - Retno Martini Widhyasih; Ria Nur Puspa Sari; Bagya Mujianto (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Diabetes mellitus (DM) is a metabolic disorder characterized by prolonged hyperglycemia with a risk of complications in the kidney. Glycemic control can be monitored by means of an HbA1c test. Poor glycemic control can lead to decreased kidney function which can be assessed from the glomerular filtration rate (GFR). GFR is measured using serum creatinine levels using the equation Modification of Diet in Renal Disease (MDRD). This study aims to determine the correlation between HbA1c levels and LFG in DM patients. The research method was observational analytic with cross sectional design on 90 medical records of DM patients in 2019 at Budhi Asih Hospital, which carried out HbA1c and serum creatinine tests as the basis for calculating LFG. Data analysis used Spearman's correlation test with a 95% CI (? = 0.05). The results showed that the average HbA1c level was 7.9%, meaning that most patients had bad HbA1c levels and the average LFG result was 60 mL/min/1.73m2, meaning that most patients had an LFG value <90 mL/min/1.73m2 and indicates a disturbance in renal function. The results of Spearman's correlation show a negative direction (r) of -0.396. It can be concluded that the higher the HbA1c level, the smaller the LFG value so that DM patients must carry out regular glycemic control to prevent a decrease in kidney function which can lead to complications.